2020–2021 Vegetable Production Handbook: Chapter 7. Cucurbit Production: HS725/CV123, rev. 4/2020 - Freeman, Josh H; McAvoy, Eugene J.; Boyd, Nathan S.; Paret, Mathews; Wang, Qingren; Miller, Christian F.; Desaeger, Johan; Qureshi, Jawwad; Martini, Xavier; Dittmar, Peter J.; et al. (EDIS, 2020)
This chapter covers production of cucurbits, such as cantaloupe, cucumber, squash, watermelon, and pumpkin.